Legal Framework for International Liability in Peaceful Nuclear Energy - Belal Ali abuhasballah (International Journal of Global Community, 2024)
In this study, we have examined the legal basis for international responsibility regarding damages resulting from the use of nuclear energy for peaceful purposes. Initially, we clarified the concept of nuclear energy in jurisprudence, international law, and domestic law. We then discussed various applications of nuclear energy for peaceful purposes. Subsequently, we highlighted the significant risks that arise from the use of nuclear energy for peaceful purposes on human health and the environment. Towards the conclusion of the study, we delved into the topic of international responsibility. We began by defining international responsibility, followed by an exploration of the legal foundation for international responsibility in this study. We deliberated on several theories, ranging from the theory of error to that of absolute responsibility. The researcher contends that the most accurate and widely accepted stance, fitting for this situation, is to adopt the theory of absolute responsibility. Accordingly, the state is held accountable for all damages resulting from its utilization of nuclear energy for peaceful purposes, irrespective of whether it violates an international legal norm or not.